Local Variability in Microbiome Composition and Growth Suggests Habitat Preferences for Two Reef-Building Cold-Water Coral Species - Chapron, Leila; Lartaud, Franck; Le Bris, Nadine; Peru, Erwan; Galand, Pierre E. (Frontiers in Microbiology, 2020)
Cold-water coral (CWC) ecosystems provide niches and nurseries for many deep-sea species. Lophelia pertusa and Madrepora oculata, two cosmopolitan species forming three dimensional structures, are found in cold waters under specific hydrological regimes that provide food and reoxygenation. There is now more information about their feeding, their growth and their associated microbiome, however, little is known about the influence of their habitat on their physiology, or on the composition of their bacterial community. The goal of this study was to test if the habitat of L. pertusa and M. oculata influenced the hosts associated bacterial communities, the corals’ survival and their skeletal growth along the slope of a submarine canyon. A transplant experiment was used, based on sampling and cross-redeployment of coral fragments at 2 contrasted sites, one deeper and one shallower. Our results show that M. oculata had significantly higher skeletal growth rates in the shallower site and that it had a specific microbiome that did not change between sites. Inversely, L. pertusa had the same growth rates at both sites, but its bacterial community compositions differed between locations. Additionally, transplanted L. pertusa acquired the microbial signature of the local corals. Thus, our results suggest that M. oculata prefer the shallower habitat.